Current state of knowledge concerning experimental applications for deep brain stimulation in specific neurologic and psychiatric disorders - Michał Senger; Patrycja Doruch; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2022)
Introduction and objectives. Deep brain stimulation  (DBS) is an invasive treatment method of certain neurologic and psychiatric disorders. It relies on sending external electrical stimulus to specific targets within the brain, causing change in their functioning. DBS is an approved management procedure, for instance in Parkinson's Disease or Obsessive-compulsive disorder. Currently, studies are being conducted on the possible utilization of DBS in other disorders, especially exhibiting resistance for standard treatment. The objective of this study, is to present the state of knowledge concerning experimental usage of DBS in specific disorders. The following study is based on the review of scientific literature for the years 2000 - 2022. State of knowledge. Regarding experimental applications, DBS is being used among others in Tourette's Syndrome, Huntington's Disease, Depression and Alzheimer's Disease. The review of the literature allows to gather data concerning initial patients selection, mechanism of action, potential benefits and thus far noted adverse effects. Evaluation of therapy efficacy is mostly limited, due to short observation periods and lack of unified patient qualification criteria for the operation.  Conclusion. Deep brain stimulation is a management method, in many cases acknowledged as safe and efficient. It is observed to have a beneficial impact on the disorders described in the following article. However, the approval of DBS as a conventional treatment requires improvement of many factors decisive of therapeutic success. Conduction of more randomised clinical trials in the future, may be helpful in achieving this objective.